2005
DOI: 10.1021/jp0557417
|View full text |Cite
|
Sign up to set email alerts
|

Molecule-Based Photonically Switched Half and Full Adder

Abstract: A single molecule logic gate using electronically excited states and ionization/fragmentation can take advantage of the differences in cross-sections for one and two photon absorption. Fault tolerant optically pumped half adder and full adder are discussed as applications. A full adder requires two separate additions, and the logic concatenation that is required to implement this is physically achieved by an intramolecular transfer along the side chain of 2-phenylethyl-N,N-dimethylamine (PENNA). Solutions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 32 publications
0
53
0
3
Order By: Relevance
“…[1][2][3] Faster implementations of logic gates based on optical addressing with laser pulses were proposed by Kompa and Levine [4] which led to further implementations of optical molecular logic machines up to a full adder and finite state machines by Levine and collaborators. [5][6][7][8][9][10] In parallel, several groups have shown that it is possible realize complex combinational logic circuits at the molecular scale, up to half and full addition or subtraction using various external perturbations, i.e., chemical, biochemical, photochemical, optical, electrochemical, electrical, to address the system, encode the inputs and perform the logic operations. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] We propose here another approach for implementing molecular logic gates.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Faster implementations of logic gates based on optical addressing with laser pulses were proposed by Kompa and Levine [4] which led to further implementations of optical molecular logic machines up to a full adder and finite state machines by Levine and collaborators. [5][6][7][8][9][10] In parallel, several groups have shown that it is possible realize complex combinational logic circuits at the molecular scale, up to half and full addition or subtraction using various external perturbations, i.e., chemical, biochemical, photochemical, optical, electrochemical, electrical, to address the system, encode the inputs and perform the logic operations. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] We propose here another approach for implementing molecular logic gates.…”
Section: Introductionmentioning
confidence: 99%
“…Aminfragmentierung (durch Photoionisierung mit anschließendem Ladungstransfer). [23] Die Inputs sind durch die beiden benötigten UV-Photonen definiert, die z. B. von zwei verschiedenen Lasern geliefert werden.…”
Section: Halbaddierer Und Volladdiererunclassified
“…[23] Ein Volladdierer kann drei binäre Ziffern summieren: zwei Inputs (I1 und I2) und den CAR-RY IN (C in ) der vorhergehenden Addition. Das erfordert zwei Halbaddierer HA mit dem Summen-Output des ersten Halbaddierers HA1 (Mittelsumme) als Input des zweiten Halbaddierers HA2 (Schema 8).…”
Section: Halbaddierer Und Volladdiererunclassified
See 1 more Smart Citation
“…Molecular realizations of simple binary gates and complex logic circuits relies on chemical [29,30], photochemical [31][32][33][34][35]36], optical [37][38][39][40], electrical [41][42][43][44] and electrochemical [45,46] addressing at the molecular scale. Finite state molecular machines, that is molecular devices that possess a memory unit whose content is processed by the computing unit together with the inputs, have also been designed [37, 43,[47][48][49].…”
mentioning
confidence: 99%